PENGEMBANGAN BAHAN AJAR APRESIASI SASTRA ANAK DI SEKOLAH DASAR - Meidiani, Ni Made; Fajriani, Anida; Suardiani, Ni Putu; Dwipayani, Ni Made Ayu; Arthaningsih, Ni Kadek Juni; Putrayasa, Ida Bagus; Sudiana, I Nyoman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of literary appreciation teaching materials in elementary schools is essential to enhance students’ interest and understanding of literary works and the moral values contained within. This study aims to analyze and design literary appreciation teaching materials that suit student characteristics and the current curriculum. The method used is qualitative descriptive with a systematic literature review, examining various scientific articles related to the development of children’s literary teaching materials. The results show that teaching materials integrating moral values, local wisdom, and interactive technology such as multimedia modules can improve the effectiveness of literary appreciation learning in elementary schools. In conclusion, the development of literary appreciation teaching materials based on local wisdom and multimedia is highly feasible to support character strengthening and literacy competence in students